Dinamika Populasi Sapi Bali di Wilayah Utara Kabupaten Parigi Moutong - Nita, Indah Mayu; Rusiyantono, Yohan; Malewa, Amiruddin Dg (Mitra Sains, 2023)
This study aims to analyze the dynamics of the Bali cattle population in the northern part of Parigi Moutong Regency, this study has been carried out in three districts, namely Bolano, Bolano Lambunu and Moutong for two months, from March to May 2022. The method used in this study is a purposive method. sampling. The parameters observed in this study are the income rate consisting of the annual birth rate, the annual purchase rate, the annual cattle subsidy/assistance and the expenditure rate including the mortality rate (mortality), slaughter and sales as well as natural growth/Natural Increase (NI). The results showed that, the income rate for the birth rate to the mother was 54.03% and the birth rate to the population was 22.41% from 362 calves born, while the purchase rate was 6.32% from 102 heads and assistance was 6.13%. of 100 heads. The expenditure rate for the sales level is 7.18% of the 116 birds sold, while the slaughter rate is 2.48% from 40 birds, the mortality rate to the broodstock is 1.94% from 670 birds and the mortality rate to the population is 0.8% from 1615. cattle, so the number in the NI value is 21.61%.